THE MARITIME ENGLISH USES IN BELAWAN PORT - Muhammad Satria; Wan Anayati; Zuindra .; Muhammad Kiki Wardana; Mayasari . (Jurnal Education and Development, 2021)
The objective of this thesis is firstly, to find out how the phenomenon of Standard Marine Communication Phrase terminology at Belawan Port. Secondly, to elucidate how the related theory of Standard Marine Communication Phrase terminology at Belawan Port. Thirdly, to analyse results of the research. In analysis Standard Marine Communication Phrase, the source of the data based from Q-Code, QAA-QNZ refers to aeronautical services, QOA-QOZ refers to maritime services, QRA-QUZ refers to all services and QZA-QZZ refers for other usage. Theoretical Framework from competence and performance proposed by Chomsky. This research used descriptive qualitative method to analyse from the data above. The finding of this research, that the dominant sentence and phrases such as Message Markers, Standard Communication Phrase and Position.